EFFECT OF NIFEDIPINE ON APOPTOSIS, NECROSIS AND VIABILITY OF GERMINAL EPITHELIAL CELLS IN THE CONTRALATERAL TESTICLE AND PLASMA TESTOSTERONE LEVELS IN MALE WHITE RATS (RATTUS NORVEGICUS, WISTAR STRAIN) AFTER UNILATERAL TESTICULAR TORSION - Mardihusodo, Hajid Rahmadianto; Rizaldi, Fikri; Hakim, Lukman (Indonesian Urological Association, 2019)
Objective: To compare the number of apoptosis, necrosis and viability of germinal epithelial cells in the contralateral testicle (CT) and plasma testosterone (PT) levels in white male rats which administered Nifedipine after unilateral testicular torsion (TT) compared with control group. Material & Methods: This research was an experimental study using male white rats (Rattus Norvegicus, Wistar strain) aged 10-12 weeks and body weight 150-200 gram. A total of 30 rats were then randomly divided into 5 groups (n=6) which were negative control group (KN), positive control group (KP1 and KP2) and Nifedipine-administered group (N1 and N2). Each group performed unilateral left side torsion of testicular of 1080o anticlockwise except the KN group. There was 4-hour ischemic duration in the KP1 and N1 groups while 10 hours in the KP2 and N2 groups. Administration of Nifedipine 30 minutes before detorsion by intraperitoneal injection dosed 100 μg/kgBW. All groups performed right orchidectomy and plasma blood sampling. Measurement of apoptosis, necrosis and viability of germinal epithelial cells in the CT using flowcytometry. Measurement of PT levels using Enzyme-Linked Immunosorbent Assay (ELISA). Results: The number of apoptosis, necrosis and viability of contralateral testicular germinal epithelial cells and PT levels in the KN group compared with KP1 and KP2 groups were significantly different (p<0.05). There was no significant discrepancy in apoptosis (p>0.05) in KP1 group compared with N1 group, as well as in KP2 group compared with N2 groups. The number of necrosis, viability of germinal epithelial cells in the CT and PT level in KP1 group in compared with N1 group, as well as in KP2 group in compared with N2 group were significantly different (p<0.05). Conclusion: Nifedipine administration prior to testicular detorsion can maintain cell viability and decrease the amount of necrotic germinal epithelial cells in the CT and prevent the decrease in PT levels after unilateral TT.